Preparation process of high-wear-resistance glass bottle

By using blast furnace slag, molten quartz powder, CeO2 powder and PMMA emulsion, and annealing and polishing cerium oxide particles, the problem of glass bottles being easily scratched and worn during transportation and use is solved, significantly improving its scratch and wear resistance, and enhancing the safety and brand trust of the product.

CN119638186APending Publication Date: 2025-03-18PUTIAN RIJING GLASS PROD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411912994.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing glass bottles are prone to scratches and wear during transportation and use, resulting in reduced physical performance, increasing product losses and safety risks, while affecting brand trust and loyalty.

Method used

Components such as blast furnace slag, molten quartz powder, CeO2 powder and PMMA emulsion are used as raw materials for glass bottles, and the flexural strength and wear resistance of glass bottles are improved through annealing and polishing of cerium oxide particles.

Benefits of technology

It significantly improves the anti-scratch and wear capability of glass bottles, reduces the risk of damage during transportation and use, and improves product safety and brand trust.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005206196850000071
    Figure BDA0005206196850000071
  • Figure BDA0005206196850000111
    Figure BDA0005206196850000111
  • Figure BDA0005206196850000121
    Figure BDA0005206196850000121
Patent Text Reader

Abstract

The invention relates to the field of glass product processing, and particularly discloses a preparation process of a high-wear-resistance glass bottle, which comprises the following steps: material preparation: crushing and grinding blast furnace slag to 0.5-0.8 mm, grinding glass powder, sieving with a 200-500-mesh sieve, and then mixing with fused quartz powder, borax, sodium carbonate, table salt, CeO2 powder and PMMA emulsion to prepare a blend; melting: heating the co-mixture until the co-mixture is molten to prepare liquid glass; liquid glass is poured into a mold and blown to be formed, and a glass bottle primary blank is prepared; and post-treatment: carrying out annealing treatment on the glass bottle primary blank, cooling to room temperature, shaping, polishing with cerium oxide particles, cleaning and drying. The glass bottle prepared by the method disclosed by the invention has the advantages of smooth surface, good wear resistance, high transparency and good anti-dazzle effect, and the generation of friction scratches can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of glass product processing, and more specifically, to a preparation process of a highly wear-resistant glass bottle. Background Art

[0002] Glass bottles are packaging containers for food, beverages and many other products. They are widely used and glass is also a very historical packaging material. With many kinds of packaging materials flooding the market, glass containers still occupy an important position in beverage packaging.

[0003] At present, the method of making glass bottles mainly includes the following steps: ① raw material pre-processing: crushing block raw materials (quartz sand, soda ash, limestone, feldspar, etc.); ② batch material preparation; ③ melting: the glass batch material is heated at high temperature (1550-1600°C) in a pool kiln or a pool furnace to form liquid glass; ④ molding: squeezing glass droplets into a preliminary mold (in order to make the droplets fall into the preliminary mold easily, a funnel is currently used); then blowing compressed air into the preliminary mold to make a bottle preliminary mold, and then transferring the bottle preliminary mold to the molding mold, and blowing compressed air again to make the final bottle shape; ⑤ heat treatment: through annealing, quenching and other processes, the stress, phase separation or crystallization inside the glass is eliminated or generated, and the structural state of the glass is changed.

[0004] Glass bottles need to be cleaned before filling with beverages, and when transported after filling with beverages, glass bottles come into contact and collide with each other or rub against other objects, causing scratches or wear on the surface of the glass bottles, which will destroy the smoothness and flatness of the surface of the glass bottles and reduce the physical properties of the glass bottles, such as compressive strength and impact resistance. During the filling, transportation and use process, these damaged glass bottles are more likely to break or leak, thereby increasing product losses and safety risks, increasing production costs and reducing production efficiency. Glass bottles with friction scratches on the surface will also leave a bad impression on consumers and reduce their trust and loyalty to the brand. Summary of the invention

[0005] In order to enhance the wear resistance of the surface of a glass bottle and reduce the occurrence of friction scratches, the present application provides a preparation process for a highly wear-resistant glass bottle.

[0006] In the first aspect, the present application provides a preparation process of a highly wear-resistant glass bottle, which adopts the following technical solution: A preparation process of a high wear-resistant glass bottle, comprising the following steps: crushing and grinding blast furnace slag to 0.5-0.8 mm, grinding glass powder through a 200-500 mesh sieve, and then mixing with fused quartz powder, borax, soda ash, salt, CeO 2 The powder and PMMA emulsion are mixed to prepare a blend; The raw materials in the blend are as follows: 55-60 parts of blast furnace slag, 5-10 parts of fused quartz powder, 30-40 parts of glass powder, 14-18 parts of borax, 12-16 parts of soda ash, 16-20 parts of salt, 7-13 parts of CeO 2 Powder and 8-12 parts PMMA emulsion; Melting: The blend is heated to melt to obtain liquid glass; Molding: Pour liquid glass into the mold and blow it into shape to produce a glass bottle embryo; Post-processing: annealing the glass bottle embryo, cooling it to room temperature to set it, polishing it with cerium oxide particles, cleaning it, and drying it.

[0007] By adopting the above technical solution, blast furnace slag, fused quartz powder, CeO 2 Powder and PMMA emulsion are used as raw materials for glass bottles. The small particle size of fused quartz powder can help improve the particle packing density, thereby improving the sintering density and the flexural strength of the glass. In addition, fused quartz powder can reduce the crystallization peak temperature and improve the crystallization ability. Blast furnace slag is steelmaking waste in the steel industry and is generally used for building materials, fertilizer catalytic materials, etc. Because it is mainly composed of oxides such as calcium oxide, aluminum oxide, magnesium oxide and silicon dioxide, it can also be used as the main component of some glass systems. The silicon dioxide contained in it can be used as a glass network former. Si 4+ The ions are connected in the form of silicon-oxygen tetrahedrons to form the basic network structure of the glass. The silicon-oxygen network structure of the glass will have different degrees of polymerization and depolymerization. Alumina acts as a network intermediate in the glass structure. Its structure can be in [AlO 4 ] and [AlO 6 ] directly affects the network structure of the glass, thereby making microcrystalline glass with high flexural strength, high volume density and high hardness.

[0008] Cerium oxide powder can further refine the grains. During the crystallization process, the dissolved rare earth elements tend to be concentrated at the grain boundaries or phase boundaries, which reduces the driving force for grain growth and limits the growth of grains. It can promote the transformation of liquid glass to a non-static structure by hindering the formation and growth of crystal nuclei, and can also improve the fluidity of liquid glass and reduce the surface tension of the melt.

[0009] PMMA emulsion acts as a binder, which can wrap the powder particles and form a three-dimensional network resin structure through self-solidification, thereby improving strength and toughness. PMMA emulsion can increase the dispersibility of various powder particles and enhance the density and scratch resistance of glass bottles. This is because ethanol and butanone solvents have good wettability for powder particles, PMMA itself has a good dispersing effect, and the molecular chain has more or less polymethyl methacrylate groups, which can be strongly adsorbed on the surface of each raw material, thereby increasing the density of the glass bottle.

[0010] In addition, cerium oxide particles are used to polish the cooled and shaped glass bottle embryos. Cerium oxide is a polishing material with excellent performance, consistent hardness, good wear resistance, and a certain cutting force. During the polishing process, cerium oxide particles can effectively remove flaws, scratches and tiny unevenness on the surface of the glass bottle, making the surface smooth and flat. This smooth and flat surface can reduce friction and wear, thereby improving the wear resistance and scratch resistance of the glass bottle.

[0011] Optionally, the PMMA emulsion comprises the following raw materials in parts by weight: 6-10 parts of PMMA, 90-94 parts of solvent, 1-4 parts of plasticizer, 1-5 parts of dispersant, and 1-1.5 parts of graphene.

[0012] By adopting the above technical scheme, ethanol and butanone are used as solvents, the wettability of PMMA emulsion to raw material particles can be increased, the mixing uniformity of the raw materials can be improved, and graphene is added to PMMA emulsion, which can serve as a reinforcing phase to increase the hardness and pressure bearing capacity of the glass bottle, and can hinder the radial expansion of cracks. Moreover, a single layer of graphene can accommodate more elastic energy, thereby improving its fracture toughness, reducing indentation crack resistance, improving crack resistance, and reducing mechanical and chemical wear, increasing density, reducing friction coefficient, and reducing contact damage and sub-surface damage.

[0013] Optionally, the glass powder has the following mass percentages of raw materials: 5-10% B 2 O 3 、20-21%Li 2 O, 35-40% SiO 2 , 2-3% ZnO, the balance is CaO.

[0014] By adopting the above technical solution, glass powder is prepared with calcium oxide and other ingredients, wherein calcium oxide can improve chemical stability and has a certain strengthening effect on the mechanical strength of glass. 2 O 3 and SiO 2 They are both network-forming bodies, but the network structures are different. They mainly play the role of skeleton. 2 O 3 It is a two-dimensional layered structure, mainly composed of [BO 3 ] are connected. When mixed with calcium oxide, the free oxygen in the blending system increases and 3 ] combined to generate [BO 4 ],[BO 4 ] can strengthen the strength of glass, and silicon dioxide is a three-dimensional structure, consisting of [SiO 4] composition, its dielectric loss is small, calcium ions can react with Si-O, which will change the original structure of the network, making it easier for particles to move. At higher temperatures, the viscosity of the liquid phase will decrease, making it easier for crystals to grow, and promoting the crystallization of microcrystalline glass. Moreover, the addition of silica can supplement the silicon content in blast furnace slag, reduce the aluminum-silicon ratio, increase silicon ions, and reduce [AlO6] in the glass structure to prevent it from destroying the degree of polymerization of the glass network. If the aluminum ion content is high and the aluminum-silicon ratio is large, the precipitation of calcium aluminum orthoclase inside the glass will increase, and the precipitation of diopside and barium cryolite will decrease, which is not conducive to improving the flexural strength of the glass. Therefore, the use of silica in glass powder can increase the content of silica in the glass product, so that enough fine nano-grains are precipitated in the glass, thereby increasing the density of the glass, effectively preventing the formation and expansion of cracks, enhancing its crack resistance, and improving the scratch resistance. Zinc oxide is a common additive in microcrystalline glass. Zinc ions can not only form a tetra-coordinated [ZnO 4 ] participate in the glass network structure, and can also [ZnO 6 ] destroys the network structure of the glass, while the zinc ions take away O 2- The ability of ZnO is strong, which is conducive to crystallization. The addition of zinc oxide will also generate white zinc sulfide, making the glass made from blast furnace slag white. ZnO will reduce the sintering activation energy of glass and promote sintering. At the same time, it is conducive to the increase of glass volume density, promote the precipitation and growth of calcium aluminum feldspar, and the growing grains are connected to each other, which is conducive to the increase of glass volume density. It can also provide "free oxygen" for the system to increase the O / Si ratio, and weaken the connection between Si-O bonds in the glass network, inducing the glass network to change from a high polymerization structure to a lower polymerization structure, which is conducive to reducing the activation energy of the glass melt and reducing the viscosity. However, if the amount of zinc oxide is too large, it will cause pores and microcracks in the glass, hinder the precipitation of diopside, promote the precipitation and growth of calcium aluminum feldspar, and is not conducive to the improvement of the flexural strength of the glass. Therefore, the structural mode in which multiple crystal phases are interspersed and nested makes the internal bonding structure of the glass complex, the bonding strength is increased, and the flexural strength is increased to a certain extent.

[0015] Optionally, the CeO 2 The amount of powder used is 10 wt % of the total amount of blast furnace slag, glass powder and fused silica powder.

[0016] By adopting the above technical solutions, CeO 2 The addition of powder to the raw materials can make the grains finer, improve the fluidity of liquid glass, increase the density and volume density of the glass bottle, and improve its hardness and wear resistance.

[0017] Optionally, the annealing treatment is divided into four stages: the first stage: maintaining at 550-650°C for 15-25 minutes; the second stage: cooling from the first stage temperature to 300-325°C at a rate of 3-5°C / min, and keeping warm for 100-120 minutes; the third stage: cooling from the second stage to 190-220°C at a rate of 3-5°C / min, and keeping warm for 50-70 minutes; the fourth stage: cooling from the third stage to 110-130°C at a rate of 3-5°C / min, and keeping warm for 120-180 minutes.

[0018] By adopting the above technical scheme, in order to ensure the annealing effect of the glass bottle, the annealing treatment is divided into 4 stages, which can fully release the internal stress of the glass bottle, prevent the glass bottle from generating new stress during the cooling process, improve production efficiency, and balance production efficiency and annealing effect.

[0019] Optionally, during the fourth annealing stage, a cold end spraying liquid is sprayed onto the glass bottle embryo, and the cold end spraying liquid includes the following raw materials in parts by weight: 1-2 parts of epoxy resin, 0.3-0.6 parts of curing agent, 0.8-1.6 parts of polytetrafluoroethylene, and 0.15-0.2 parts of nano-organic silicon particles composite PVDF nanofibers.

[0020] By adopting the above technical scheme, in the fourth stage of annealing, a cold end spraying liquid is sprayed onto the glass bottle embryo by a spraying method, and the cold end spraying liquid contains epoxy resin, polytetrafluoroethylene, etc. The epoxy resin can form a lubricating and transparent coating on the glass bottle embryo, and the addition of polytetrafluoroethylene can further improve the lubricity of the coating, reduce the generation of friction, reduce the wear rate, and increase the scratch resistance; the nano-organic silicon particles and PVDF nanofibers are composited, and the addition of nano-organic silicon particles can improve the interface force between the composite PVDF nanofibers and the epoxy resin, thereby improving the scratch resistance, because the nano-organic silicon particles are loaded in the PVDF nanofibers, and the Si-OR functional group is hydrolyzed into a silanol group during the reaction, and then a silicon-oxygen-silicon group is formed through hydrolysis and condensation. Bond, providing a uniformly distributed inorganic network for the coating formed by the cold-end spraying liquid, thereby making the mechanical properties of the coating more excellent, and the amino group reacts with the epoxy group in the epoxy resin, so that the silicone particles are embedded in the coating in the form of chemical bonds, which enhances the interface performance between PVDF nanofibers and epoxy resin, thereby being evenly distributed in the coating, improving the cohesive strength and bearing capacity of the coating, effectively improving the coating's resistance to crack propagation, enhancing the coating's hardness, reducing the wear rate, reducing deformation under friction stress, and improving resistance to plastic deformation. If the nano silicone particles are directly mixed with the epoxy resin, the surface roughness of the coating may be increased due to the surface migration effect and surface enrichment of the nano particles. Although the anti-glare effect can be improved, it will cause increased surface wear and decreased scratch resistance.

[0021] Epoxy resin, polytetrafluoroethylene and nano-organic silicon particles composite PVDF nanofibers are mixed and sprayed on the glass bottle embryo to form a coating with good transparency and anti-glare effect. The anti-glare effect can be achieved because of the light scattering of the nano-organic silicon particles, and the small particle size of the nano-organic silicon particles and PVDF nanofibers will not form tiny concave and convex structures on the surface of the glass bottle. The cold-end spray liquid forms a relatively smooth coating, but it can still make the light produce diffuse scattering reflection when projected onto the surface of the glass bottle, thereby reducing the interference of ambient light and achieving the effect of frosting and anti-glare.

[0022] Optionally, the preparation method of the nano-organic silicon particles composite PVDF nanofiber is as follows: The PVDF is dissolved to prepare a base solution with a concentration of 10-12 wt%, and the MOF material and nano-organic silicon particles are added and mixed evenly to prepare a spinning solution, and the base fiber is prepared by electrospinning, wherein the mass ratio of the MOF material, the nano-organic silicon particles and the PVDF is 0.03-0.05:0.02-0.06:1; The base fiber is immersed in a treatment solution made of PDMS and a curing agent in a mass ratio of 10:1, then taken out and dried at 80-90° C. for 10-12 hours.

[0023] By adopting the above technical scheme, PVDF nanofibers can be used as a light diffusion layer on the surface of the glass bottle in the cold end spray liquid, and the size range of the PVDF nanofibers on the micro-nano scale is equivalent to the wavelength of visible light, which helps to improve the light scattering ability. The nanofibers with high orientation show good light diffusion ability and optical anisotropy. The surface of the PVDF fibers made by adding nano-organic silicon particles and MOF materials is smooth and the diameter is uniform, and the light scattering ability can be further improved. In addition, the nanofibers made by electrospinning have high porosity and high specific surface area, so that the nanoparticles have more attachment sites, which can avoid the problems of agglomeration and uneven dispersion of single nanoparticles. Therefore, the addition of nano-organic silicon particles and MOF materials can increase the roughness of the surface of a single fiber, improve the light scattering degree of a single fiber, increase the number of light refractions, which is not conducive to the transmission of light, and thus make the production The average light transmittance of the basic fiber has decreased, but the metal skeleton material has a strong absorbance in the ultraviolet band, so the glass bottle has the ability to block ultraviolet radiation and effectively prevent the strong ultraviolet rays from irradiating the glass bottle; and after adding MOF material and nano-organic silicon particles, the transmittance of the composite PVDF fiber is improved after being infiltrated with PMDS treatment liquid, because the solid-solid interface between the fiber and PDMS is moved to the solid-gas interface between the fiber and the air; the haze is increased, so the added nanoparticles are distributed along the fiber, so that the fiber can produce more light scattering, and after the PDMS infiltration treatment, the surface of the composite nanofiber is smooth and hydrophobic, and it can be evenly dispersed in the mixture of epoxy resin and polytetrafluoroethylene, and after PDMS treatment, the composite PVDF nanofiber has good adhesion, which can increase the adhesion effect of the cold-end spray liquid to form a coating and the glass bottle.

[0024] Optionally, the melting temperature is 1300-1550°C, the melting time is 2-4h, and the heating rate is 200-300°C / h.

[0025] By adopting the above technical solution and melting at the above temperature for a specific time, the fluidity and plasticity of the liquid glass can be improved, so that it can be fully filled into the mold to form a glass bottle with a complete shape and a smooth surface.

[0026] Optionally, the polishing method is as follows: polishing with cerium oxide particles with a particle size of 1 μm for 8-10 hours, then polishing with cerium oxide particles with a particle size of 0.5 μm for 4-5 hours, and finally polishing with cerium oxide particles with a particle size of 0.3 μm for 4-5 hours.

[0027] By adopting the above technical solution, the particle size of the cerium oxide particles used for polishing is gradually reduced, and the surface of the glass bottle can be gradually polished to increase the smoothness of the surface of the glass bottle, and a scratch inhibition effect can be produced to reduce the occurrence of scratches.

[0028] Optionally, the drying temperature is 50-70° C., and the drying time is 8-12 hours.

[0029] By adopting the above technical solution, the cleaning water at 50-70° C. has a stronger ability to wet the surface of the glass bottle, which can improve the cleaning effect.

[0030] In summary, this application has the following beneficial effects: 1. Since this application uses blast furnace slag, fused quartz powder, PMMA emulsion and CeO 2 The process of preparing glass bottles is carried out by using cerium oxide particles to polish the primary embryo using cerium powder as raw materials. Since the composition of blast furnace slag is stable and similar to that of microcrystalline glass, it is mixed with molten quartz powder and other raw materials to produce glass bottles with high volume density, high flexural strength, strong surface scratch resistance, and not easy to produce friction and wear. It reduces the defects such as abrasions and potholes on the surface of the glass bottles due to collisions and scratches during transportation and use, and prevents the breakage of glass bottles, leakage of contents, and even bottle explosion and injury caused by abrasions and impacts.

[0031] 2. In the present application, graphene is preferably added to the PMMA emulsion, which can increase the hardness and pressure bearing capacity of the glass bottle, reduce the friction coefficient, increase the density, hinder the crack propagation, increase the fracture toughness, and improve the indentation resistance.

[0032] 3. The method of the present application adopts four-stage annealing, and during the fourth stage of annealing, a cold-end spraying liquid containing epoxy resin, polytetrafluoroethylene, nano-organic silicon particles and composite PVDF nanofibers is sprayed, which can form a transparent and smooth coating on the glass bottle embryo, thereby further enhancing the anti-scratch, anti-mark and wear resistance of the glass bottle, and at the same time, the glass bottle has a certain anti-glare effect, which can reduce visual fatigue and improve visual effects. DETAILED DESCRIPTION

[0033] The following examples further illustrate the present application in detail.

[0034] Preparation Example 1-7 of Cold End Spraying Liquid In Preparation Example 1, the epoxy resin is selected from Kain Chemical, model number is Hansen 6520-WH-53A from the United States, diethylenetriamine is selected from Kain Chemical, model number is DEH20, polytetrafluoroethylene is selected from Guangzhou Jiushun New Materials, model number is Daikin TT-7400 from Japan, PVDF is selected from Solvay from the United States, model number is Solef6010, MIL-101 (Cr) is selected from Xi'an Qiyue Biology, CAS number is 869288-09-5, PDMS and curing agent are selected from Dow Corning, model number is DC184.

[0035] Preparation Example 1: 2kg of epoxy resin, 0.6kg of diethylenetriamine, 1.6kg of polytetrafluoroethylene and 0.2kg of nano-organic silicon particles composite PVDF nanofibers are mixed evenly. The preparation method of nano-organic silicon particles composite PVDF nanofibers is as follows: (1) 10g of PVDF is dissolved in DMF and acetone with a volume ratio of 7:3 to prepare a base liquid with a concentration of 10wt%, MOF material and nano-organic silicon particles are added, mixed evenly, and a spinning solution is prepared. After electrospinning, a base fiber is obtained. The spinning rate is 0.8mL / h, the receiving distance is 20cm, the spinning voltage is 16kv, the spinning time is 4h, and the mass ratio of MOF material and nano-organic silicon particles to PVDF is 0.05:0.02:1; MOF material is MIL-101 (Cr), and the preparation method of nano-organic silicon particles is: 2.5g KH550 was added to deionized water, ethanol and ethyl orthosilicate in a molar ratio of 4:8:1, and hydrochloric acid was added to adjust the pH to 3. After stirring for 15 min, the mixture was vacuum dried at 70 °C for 24 h. (2) The base fiber was immersed in a treatment solution made of PDMS and a curing agent in a mass ratio of 10:1, then taken out and dried at 80°C for 12 h.

[0036] Preparation Example 2: 1kg epoxy resin, 0.3kg diethylenetriamine, 0.8kg polytetrafluoroethylene and 0.1kg nano-organic silicon particles composite PVDF nanofibers are mixed evenly. The preparation method of nano-organic silicon particles composite PVDF nanofibers is as follows: 12g PVDF is dissolved in DMF and acetone with a volume ratio of 7:3 to prepare a base liquid with a concentration of 12wt%, MOF material and nano-organic silicon particles are added, mixed evenly, and a spinning solution is prepared. After electrostatic spinning, a basic fiber is obtained. The mass ratio of MOF material and nano-organic silicon particles to PVDF is 0.03:0.06:1; the spinning rate is 0.8mL / h, the receiving distance is 20cm, the spinning voltage is 16kv, the spinning is 4h, the MOF material is MIL-101 (Cr), and the preparation method of nano-organic silicon particles is: 2.5g KH550 was added to deionized water, ethanol and ethyl orthosilicate in a molar ratio of 4:8:1, and hydrochloric acid was added to adjust the pH to 3. After stirring for 15 min, the mixture was vacuum dried at 80 °C for 22 h. (2) The base fiber was immersed in a treatment solution made of PDMS and a curing agent in a mass ratio of 10:1, then taken out and dried at 90°C for 10 h.

[0037] Preparation Example 3: The difference from Preparation Example 1 is that no polytetrafluoroethylene is added.

[0038] Preparation Example 4: The difference from Preparation Example 1 is that no nano-organic silicon particles composite PVDF nanofibers are added.

[0039] Preparation Example 5: The difference from Preparation Example 1 is that no nano-organosilicon particles and MOF materials are added to the nano-organosilicon particles composite PVDF nanofibers.

[0040] Preparation Example 6: The difference from Preparation Example 1 is that no MOF material is added to the nano-organosilicon particle composite PVDF nanofiber.

[0041] Preparation Example 7: The difference from Preparation Example 1 is that immersion in PDMS treatment solution is not used. Example

[0042] The specific oxide composition of the blast furnace slag in Example 1 is shown in Table 1, which is selected from Shijiazhuang Xuhan New Materials, model xh78, the fused quartz powder is selected from Xuzhou Yingtuo New Materials, model yt-31, mesh number 800, and graphene is selected from Xianfeng Nano, item number 100002, and serial number XF001W.

[0043] Table 1 Composition of blast furnace slag Embodiment 1: A process for preparing a highly wear-resistant glass bottle, comprising the following steps: S1. Material preparation: 5.5 kg blast furnace slag was crushed and ground to 0.5 mm, 4 kg glass powder was ground at a speed of 250 r / min for 30 min and then passed through a 500 mesh sieve, and then mixed with 0.5 kg fused quartz powder, 1.8 kg borax, 1.6 kg soda ash, 2 kg salt, 1 kg CeO 2 The powder was mixed with 0.8 kg of PMMA emulsion to prepare a blend; PMMA emulsion was prepared by mixing 0.6 kg PMMA, 9.4 kg solvent (ethanol and butanone in a mass ratio of 1:1), 0.4 kg plasticizer (butyl benzyl phthalate), 0.5 kg dispersant (castor oil), and 0.15 kg graphene for 10 min; Preparation of glass powder: Mix the following components in weight percentage: 5% B 2 O 3 、21%Li 2 O, 40% SiO 2 , 3% ZnO and 31% CaO were mixed to obtain a mixed powder, 200 g of the mixed powder was weighed, the temperature was raised to 1450°C at 5°C / min, kept at this temperature for 1 hour, poured into clean water, and then dried at 80°C; S2, melting: heating the blended material to 1550°C at a rate of 200°C / h, and keeping the temperature for 2h to melt the blended material to obtain liquid glass; S3, melting: pouring liquid glass into the mold, sending it into the molding equipment and blowing it into shape to obtain the glass bottle embryo; S4. Post-treatment: anneal the glass bottle embryo, then cool it to room temperature, polish it with cerium oxide particles, spray it with clean water, and finally dry it at 70°C for 8 hours, wherein the annealing treatment has 4 stages: the first stage: maintain at 550°C for 25 minutes; the second stage: cool down from the first stage temperature to 300°C at a rate of 5°C / min, and keep it warm for 120 minutes; the third stage: cool down from the second stage temperature to 190°C at a rate of 5°C / min, and keep it warm for 70 minutes; the fourth stage: cool down from the third stage to 110°C at a rate of 5°C / min, and keep it warm for 180 minutes. The cerium oxide particle polishing method is as follows: use cerium oxide particles with a particle size of 1μm to polish for 10 hours, then use cerium oxide particles with a particle size of 0.5μm to polish for 5 hours, and finally use cerium oxide particles with a particle size of 0.3μm to polish for 5 hours.

[0044] Embodiment 2: A process for preparing a highly wear-resistant glass bottle, comprising the following steps: S1. Material preparation: 6 kg of blast furnace slag was crushed and ground to 0.8 mm, 3 kg of glass powder was ground at a speed of 250 r / min for 30 min and then passed through a 200 mesh sieve, and then mixed with 1 kg of fused quartz powder, 1.4 kg of borax, 1.2 kg of soda ash, 1.6 kg of salt, 0.7 kg of CeO 2 The powder was mixed with 1.2 kg of PMMA emulsion to prepare a blend; PMMA emulsion was prepared by mixing 1 kg PMMA, 9 kg solvent (ethanol and butanone in a mass ratio of 1:1), 0.1 kg plasticizer (butyl benzyl phthalate), 0.1 kg dispersant (castor oil), and 0.1 kg graphene for 10 min; Preparation of glass powder: Mix the following components in weight percentage: 10% B 2 O 3 、20%Li 2 O, 35% SiO 2 , 2% ZnO and 33% CaO were mixed to obtain a mixed powder, 200 g of the mixed powder was weighed, the temperature was raised to 1450°C at 5°C / min, kept at this temperature for 1 hour, poured into clean water, and then dried at 80°C; S2, melting: heating the blended material to 1300°C at a rate of 300°C / h, and keeping the temperature for 4 hours to melt the blended material to obtain liquid glass; S3, melting: pouring liquid glass into the mold, sending it into the molding equipment and blowing it into shape to obtain the glass bottle embryo; S4. Post-treatment: anneal the glass bottle embryo, then cool it to room temperature, polish it with cerium oxide particles, spray it with clean water, and finally dry it at 50°C for 12 hours. The annealing treatment has four stages: the first stage: keep it at 650°C for 15 minutes; the second stage: cool down from the first stage temperature to 325°C at a rate of 3°C / min, and keep it warm for 100 minutes; the third stage: cool down from the second stage temperature to 220°C at a rate of 3°C / min, and keep it warm for 50 minutes; the fourth stage: cool down from the third stage to 130°C at a rate of 3°C / min, and keep it warm for 120 minutes. The cerium oxide particle polishing method is as follows: use cerium oxide particles with a particle size of 1μm to polish for 9 hours, then use cerium oxide particles with a particle size of 0.5μm to polish for 4.5 hours, and finally use cerium oxide particles with a particle size of 0.3μm to polish for 4.5 hours.

[0045] Embodiment 3: A process for preparing a highly wear-resistant glass bottle, comprising the following steps: S1. Material preparation: 5.8 kg blast furnace slag was crushed and ground to 0.6 mm, 3.4 kg glass powder was ground at a speed of 250 r / min for 30 min and then passed through a 400 mesh sieve, and then mixed with 0.8 kg fused quartz powder, 1.6 kg borax, 1.4 kg soda ash, 1.8 kg salt, 1.3 kg CeO 2 The powder was mixed with 1 kg of PMMA emulsion to prepare a blend; PMMA emulsion was prepared by mixing 0.8 kg PMMA, 9.2 kg solvent (ethanol and butanone in a mass ratio of 1:1), 0.2 kg plasticizer (butyl benzyl phthalate), 0.3 kg dispersant (castor oil), and 0.13 kg graphene for 10 min; Preparation of glass powder: Mix the following components in weight percentage: 8% B 2 O 3 、20%Li 2 O, 38% SiO 2 , 2.5% ZnO and 31.5% CaO were mixed to obtain a mixed powder, 200 g of the mixed powder was weighed, the temperature was increased to 1450°C at 5°C / min, kept at this temperature for 1 hour, poured into clean water, and then dried at 80°C; S2, melting: heating the blended material to 1450°C at a rate of 250°C / h, and keeping the temperature for 3h to melt the blended material to obtain liquid glass; S3, melting: pouring liquid glass into the mold, sending it into the molding equipment and blowing it into shape to obtain the glass bottle embryo; S4. Post-treatment: anneal the glass bottle embryo, then cool it to room temperature, polish it with cerium oxide particles, spray it with clean water, and finally dry it at 60°C for 10 hours. The annealing treatment has four stages: the first stage: keep it at 600°C for 20 minutes; the second stage: cool down from the first stage temperature to 310°C at a rate of 4°C / min, and keep it warm for 110 minutes; the third stage: cool down from the second stage temperature to 200°C at a rate of 4°C / min, and keep it warm for 60 minutes; the fourth stage: cool down from the third stage to 120°C at a rate of 4°C / min, and keep it warm for 160 minutes. The cerium oxide particle polishing method is as follows: use cerium oxide particles with a particle size of 1μm to polish for 9 hours, then use cerium oxide particles with a particle size of 0.5μm to polish for 4.5 hours, and finally use cerium oxide particles with a particle size of 0.3μm to polish for 4.5 hours.

[0046] Example 4: A process for preparing a highly abrasion-resistant glass bottle, which is different from Example 1 in that no graphene is added to the PMMA emulsion.

[0047] Example 5: A process for preparing a highly wear-resistant glass bottle, which differs from Example 1 in that silicon dioxide is used in place of zinc oxide in the glass powder.

[0048] Example 6: A process for preparing a highly abrasion-resistant glass bottle, which differs from Example 1 in that calcium oxide is used in place of silicon dioxide in the glass powder.

[0049] Example 7: A preparation process for a highly wear-resistant glass bottle. The difference from Example 1 is that in the fourth annealing stage, a cold-end spraying liquid is evenly sprayed onto the glass bottle embryo. The cold-end spraying liquid is made from Preparation Example 1. During spraying, the distance between the nozzle and the glass bottle is 350 mm, the nozzle movement speed is 1.2 m / min, and the thickness of the film layer formed after spraying is 150 nm.

[0050] Example 8: A preparation process for a highly wear-resistant glass bottle. The difference from Example 1 is that in the fourth annealing stage, a cold-end spraying liquid is evenly sprayed onto the glass bottle embryo. The cold-end spraying liquid is prepared from Preparation Example 2. During spraying, the distance between the nozzle and the glass bottle is 300 mm, the nozzle moves at a speed of 1 m / min, and the thickness of the film layer formed after spraying is 200 nm.

[0051] Example 9: A preparation process for a highly wear-resistant glass bottle, which is different from Example 7 in that the cold-end spraying liquid is prepared by Preparation Example 3.

[0052] Example 10: A preparation process for a highly wear-resistant glass bottle, which is different from Example 7 in that the cold-end spraying liquid is prepared by Preparation Example 4.

[0053] Example 11: A preparation process for a highly wear-resistant glass bottle, which is different from Example 7 in that the cold-end spraying liquid is prepared by Preparation Example 5.

[0054] Example 12: A preparation process for a highly wear-resistant glass bottle, which is different from Example 7 in that the cold-end spraying liquid is prepared by Preparation Example 6.

[0055] Example 13: A preparation process for a highly wear-resistant glass bottle, which is different from Example 7 in that the cold-end spraying liquid is prepared by Preparation Example 7.

[0056] Comparative Example Comparative Example 1: A process for preparing a highly abrasion-resistant glass bottle, which differs from Example 1 in that no PMMA emulsion is added. Comparative Example 2: A process for preparing a highly abrasion-resistant glass bottle, which differs from Example 1 in that no glass powder is added.

[0057] Comparative Example 3: A preparation process of a highly wear-resistant glass bottle, which differs from Example 1 in that CeO is not added. 2 powder.

[0058] Comparative Example 4: A process for preparing a highly wear-resistant glass bottle, which differs from Example 1 in that cerium oxide particles are not used for polishing.

[0059] Performance testing Glass bottles were prepared according to the methods in the examples and comparative examples, and the properties of the glass bottles were tested according to the following methods. The test results are recorded in Table 2.

[0060] 1. Scratch depth: A constant load scratch test was performed using a multifunctional material surface performance tester (MFT4000, Lanzhou Huahui Instrument Technology Co., Ltd., China) with a constant load of 21 N and a loading speed of 10 N / s. The scratch length measured during the test was 5 mm.

[0061] 2. Wear rate: The test was conducted using an HDR-2M reciprocating friction and wear tester in a ball-disc contact form with a dual ball on top. The test was conducted under conditions of 5N load, 5Hz, and a friction distance of 180mm. The RtecMFT-5000 multifunctional friction tester was used to perform a contour scan of the friction track to obtain the three-dimensional data of the corresponding wear marks. The data was analyzed using Gwyddion three-dimensional analysis software to obtain the wear volume. The wear rate was calculated using the following formula: δ = V / L·s, where δ is the volume wear rate, unit: mm 3 / N·m; V is the wear volume obtained by data software analysis, unit: mm 3 ; s is the friction distance, calculated by frequency and time, unit: m; L is the positive load applied to the coating, unit: N.

[0062] 3. Flexural strength: The flexural strength of the sample is measured by the three-point bending method. The instrument is a KZY-300 flexural testing machine, Tianjin Luda Construction Instrument Co., Ltd. The calculation method is as follows: P = 3FL / 2bh 2 , where P is the flexural strength of the specimen (MPa), F is the maximum load when the specimen breaks (N), L is the distance between the two supporting points, that is, the span (mm), b is the width of the specimen fracture (mm), and h is the height of the specimen fracture (mm).

[0063] 4. Transmittance: The transmittance of the samples was characterized by a UV-2550 ultraviolet-visible spectrometer (UV-Vis). The transmittance within 600 nm was measured. Each sample was tested 5 times, and the average value was calculated as the test result.

[0064] 5. Reflectivity: The reflectivity at 550 nm was measured using BYK Gardner TCS II.

[0065] Table 2 Performance test results of high wear-resistant glass bottles Combining Examples 1-3 and the data in Table 1, it can be seen that the use of blast furnace slag, fused silica powder, glass powder and CeO 2 Glass bottles are made from powder and other raw materials through processes such as preparation, melting, blow molding and post-processing. The glass bottles have a smooth surface, small scratch depth, low wear rate, high flexural strength, strong drop resistance, high transparency, low reflectivity and good anti-glare properties.

[0066] Compared with Example 1, Example 4 does not add graphene to the PMMA emulsion. From the comparison of the data in Table 2, it can be seen that the scratch depth of the glass bottle made in Example 4 increases, the wear rate increases, and the wear resistance decreases slightly, but the transparency of the glass bottle increases, the reflectivity increases, and the anti-glare effect decreases.

[0067] In Example 5, silicon dioxide is used instead of zinc oxide, while in Example 6, calcium oxide is used instead of silicon dioxide. It can be seen that the scratch depth on the surface of the glass bottles prepared in Examples 5 and 6 increases, the wear resistance decreases, and the flexural strength decreases, indicating that using appropriate amounts of silicon dioxide, zinc oxide and other ingredients in the glass powder can improve the flexural strength of the glass bottle and enhance its surface scratch resistance.

[0068] Compared with Example 1, Examples 7 and 8 are also sprayed with the cold end spray liquid prepared in Preparation Example 1 and Preparation Example 2 respectively during the fourth annealing stage. As can be seen from the data in Table 2, the scratch depth on the surface of the glass bottles prepared in Examples 7 and 8 is reduced, and the wear rate is reduced. In addition, the reflectivity is further reduced while the transmittance does not change much, thereby increasing the frosting effect and anti-glare effect.

[0069] Compared with Example 7, Example 9 uses the cold end spray liquid prepared in Preparation Example 3, in which no polytetrafluoroethylene is added. It can be seen that the transparency of the glass bottle prepared in Example 9 is slightly increased, but the flexural strength is reduced, the wear rate is increased, and the surface lubrication effect is slightly decreased.

[0070] In Example 10, the cold-end spray liquid prepared in Preparation Example 4 was used. In Preparation Example 4, nano-organic silicon particles composite PVDF nanofibers were not added. It can be seen that the transparency was slightly increased, the scratch depth and the wear rate were increased, but the reflectivity was also increased, and the anti-glare effect decreased, indicating that the addition of nano-organic silicon particles composite PVDF nanofibers will slightly affect the light transmittance of the glass bottle, but will increase the anti-glare effect.

[0071] In Example 11, the cold-end spraying liquid prepared in Preparation Example 5 was used. Compared with Preparation Example 1, nano-organosilicon particles and MOF materials were not added to the nano-organosilicon particles composite PVDF nanofibers. Compared with Example 7, the cold-end spraying liquid in Example 12 was prepared by Preparation Example 6, and no MOF materials were added to the nano-organosilicon composite PVDF nanofibers. It can be seen that the reflectivity of the glass bottles prepared in Examples 11 and 12 was reduced, and the transparency was slightly improved, indicating that although the addition of nano-organosilicon particles and MOF materials slightly affected the light transmittance of the glass bottles, it could effectively improve the anti-glare effect of the glass bottles.

[0072] In Example 13, the cold end spray liquid prepared in Preparation Example 7 was used. Compared with Preparation Example 1 in Example 7, the PDMS treatment liquid was not used to impregnate the base fiber in Preparation Example 7. It can be seen that the transparency of the glass bottle prepared in Example 13 decreased, the reflectivity did not change much, and the flexural strength decreased slightly.

[0073] Compared with Example 1, in Comparative Example 1, no PMMA emulsion was added. It can be seen that the anti-glare ability of the prepared glass bottle is reduced, and the flexural strength and wear rate are reduced, and the scratch depth is increased, indicating that the wear resistance is reduced.

[0074] No glass powder was added in Comparative Example 2. Compared with Example 1, the scratch depth of the glass bottle made in Comparative Example 2 increased, the wear rate increased, the flexural strength decreased, and the wear resistance and surface smoothness of the glass bottle decreased.

[0075] In Comparative Example 3, CeO2 powder was not added. Compared with Example 1, the scratch depth of the glass bottle increased, the flexural strength decreased, and the wear resistance decreased.

[0076] In Comparative Example 4, cerium oxide particles were not used to polish the glass bottle blank. It can be seen that the surface smoothness of the glass bottle obtained in Comparative Example 4 decreased, the scratch depth increased, the wear rate increased slightly, and the changes in the flexural strength were not obvious.

[0077] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A process for preparing a highly wear-resistant glass bottle, characterized in that: The following steps are involved: Preparation of materials: crush and grind blast furnace slag to 0.5-0.8 mm, grind glass powder through 200-500 mesh sieve, and then mix with fused quartz powder, borax, soda ash, salt, CeO2 powder and PMMA emulsion to prepare a blend; The raw materials in the blend are calculated by weight as follows: 55-60 parts of blast furnace slag, 5-10 parts of fused quartz powder, 30-40 parts of glass powder, 14-18 parts of borax, 12-16 parts of soda ash, 16-20 parts of salt, 7-13 parts of CeO2 powder and 8-12 parts of PMMA emulsion; Melting: The blend is heated to melt to obtain liquid glass; Molding: Pour liquid glass into the mold and blow it into shape to produce a glass bottle embryo; Post-processing: annealing the glass bottle embryo, cooling it to room temperature to set it, polishing it with cerium oxide particles, cleaning it, and drying it.

2. The process for preparing a highly wear-resistant glass bottle according to claim 1, characterized in that: The PMMA emulsion comprises the following raw materials in parts by weight: 6-10 parts of PMMA, 90-94 parts of solvent, 1-4 parts of plasticizer, 1-5 parts of dispersant, and 1-1.5 parts of graphene.

3. The process for preparing a highly wear-resistant glass bottle according to claim 1, characterized in that: The glass powder comprises the following raw materials in percentage by weight: 5-10% B2O3, 20-21% Li2O, 35-40% SiO2, 2-3% ZnO, and the balance is CaO.

4. The process for preparing a highly wear-resistant glass bottle according to claim 1, characterized in that: The amount of CeO2 powder used is 10wt% of the total amount of blast furnace slag, glass powder and fused quartz powder.

5. The process for preparing a highly wear-resistant glass bottle according to claim 1, characterized in that: The annealing treatment is divided into four stages: the first stage: maintaining at 550-650°C for 15-25 minutes; the second stage: cooling from the first stage temperature to 300-325°C at a rate of 3-5°C / min, and keeping warm for 100-120 minutes; the third stage: cooling from the second stage to 190-220°C at a rate of 3-5°C / min, and keeping warm for 50-70 minutes; the fourth stage: cooling from the third stage to 110-130°C at a rate of 3-5°C / min, and keeping warm for 120-180 minutes.

6. The process for preparing a highly wear-resistant glass bottle according to claim 5, characterized in that: In the fourth annealing stage, a cold end spraying liquid is sprayed onto the glass bottle embryo, wherein the cold end spraying liquid comprises the following raw materials in parts by weight: 1-2 parts of epoxy resin, 0.3-0.6 parts of curing agent, 0.8-1.6 parts of polytetrafluoroethylene, and 0.15-0.2 parts of nano-organic silicon particles composite PVDF nanofibers.

7. The process for preparing a highly wear-resistant glass bottle according to claim 6, characterized in that: The preparation method of the nano-organic silicon particle composite PVDF nanofiber is as follows: The PVDF is dissolved to prepare a base solution with a concentration of 10-12 wt%, and the MOF material and nano-organic silicon particles are added and mixed evenly to prepare a spinning solution, and the base fiber is prepared by electrospinning, wherein the mass ratio of the MOF material, the nano-organic silicon particles and the PVDF is 0.03-0.05:0.02-0.06:1; The base fiber is immersed in a treatment solution made of PDMS and a curing agent in a mass ratio of 10:1, then taken out and dried at 80-90° C. for 10-12 hours.

8. The process for preparing a highly wear-resistant glass bottle according to claim 1, characterized in that: The melting temperature is 1300-1550° C., the melting time is 2-4 hours, and the heating rate is 200-300° C. / h.

9. The process for preparing a highly wear-resistant glass bottle according to claim 1, characterized in that: The polishing method is as follows: using cerium oxide particles with a particle size of 1 μm for polishing for 8-10 hours, then using cerium oxide particles with a particle size of 0.5 μm for polishing for 4-5 hours, and finally using cerium oxide particles with a particle size of 0.3 μm for polishing for 4-5 hours.

10. The process for preparing a highly wear-resistant glass bottle according to claim 1, characterized in that: The drying temperature is 50-70° C., and the drying time is 8-12 hours.